Trojan Horse Method: recent results in nuclear astrophysics. (July 2015) - Spitaleri, C; Lamia, L; Santo, M Gimenez Del; Burjan, V; Carlin, N; Li, Chengbo; Cherubini, S; Crucilla, V; Gulino, M; Hons, Z; Kroha, V; Irgaziev, B; et al.
Abstract: The accurate knowledge of thermonuclear reaction rates is important in understanding the energy generation, the neutrinos luminosity and the synthesis of elements in stars. The physical conditions under which the majority of astrophysical reactions proceed in stellar environments make it difficult or impossible to measure them under the same conditions in the laboratory. That is why different indirect techniques are being used along with direct measurements. The Trojan Horse Method (THM) is introduced as an independent technique to obtain the bare nucleus astrophysical S(E)-factor. As examples the results of recent the application of THM to the 2 H( 11 B, σ0 8 Be)n and 2 H( 10 B, σ0 7 Be)n reactions are presented.